A Study on Lexicons Used in Metajen Tradition in Sukadana Village, Karangasem Regency - I Komang Japar Aridana; I Gede Budasi; Dewa Putu Ramendra (Universitas Muhammadiyah Kalimantan Timur, 2024)
This research aims to know the types of lexicons used during the Metajen tradition in Sukadana Village, Karangasem Regency. This study is a qualitative study using 2 (two) experts in this field, namely the elderly (penua) and also the local village apparatus. The instruments in this study are the researchers themselves, the observation sheet, the interview guide, the recording tool and the phone camera. From this study, a number of lexicons and cultural meanings can be found in the study: a total of 64 (sixty-four), displayed in (24) lexicon about type or roosters, fourteen (14) Lexicons about betting code, eight (8) lexicons about instruments used, (7) lexicon for roles of people in the tradition, and eleven (11) lexicons of type of taji or sharp knives used and how it is being installed in the feet of the roosters. The cultural meaning of this activity was a component of a cultural ceremonies known as the mecaru ceremony or Tabuh Rah, which is identical to the Hindu ceremony specifically any Bhuta Yadnya upakara.